Windows XP Gigabook for Dummies - Weverka, Peter (Wiley Publishing, 2011)
What’s a Gigabook? A collection of just about everything you need to know on a topic, all in one convenient place! Windows XP Gigabook For Dummies takes the best from five other For Dummies books and squeezes out everything but the most important stuff. This single super-sized reference — more than 800 pages’ worth — gives you a go-to guide on everything connected with Windows XP, PCs and peripherals, the Internet, Office 2003, and Money 2004. You might think of it as a “greatest hits” collection.